Tailored fabrication of triple-surface-features in well-crystalline BiOCl photocatalyst and their synergistic role in catalytic processes. Issue 7 (10th March 2020) - Shahid, Malik Zeeshan; Yu, Liu; Mehmood, Rashid
Abstract : The exposed active surface sites in photocatalysts, comprising low-coordinated atomic steps and atomic-level thickness, are vital to achieve efficient catalysis. Abstract : The exposed active surface sites in photocatalysts, comprising low-coordinated atomic steps and atomic-level thickness, are vital to achieve efficient catalysis. Here we prepare well-crystalline BiOCl nanoplates incorporating distinct triple-surface-features including ultrathin thickness, channeled self-assembly and multiple atomic steps (BiOCl-UCNP) via shape controlled synthesis. The interplay between the surface and catalytic processes is disclosed. Unlike conventional BiOCl photocatalysts with individual surface-features, the triple-surface-features in BiOCl-UCNP functioned simultaneously as active sites. Briefly, the ultrathin features (2–3 nm) endow BiOCl-UCNP with a large specific surface area (14.4 m 2 g −1 ), narrower energy bandgap (3.05 eV), plentiful oxygen vacancies (OVs), and a shorter migration path for photoinduced electrons. Abundant channels improve the light absorption and distribution, enhance the molecule's adsorption capability, and strengthen the internal electric field in the layers of BiOCl-UCNP. The low-coordinated multiple atomic steps serve as highly reactive catalytic centers and expedite the separation of photogenerated electron–holes instead of recombination. Consequently, under simulated solar light, by using very low dosage (5 mg), BiOCl-UCNP exhibits exceptional efficiency (>99%) to degrade organic dyes, industrial pollutants, and antibiotics. In addition, BiOCl-UCNP achieved excellent reusability up to 8 cycles and morphological stability. These findings may advance our understanding of the interplay between the surface and photocatalytic activity in layered materials.